Effect of a Quality of Care Improvement Initiative in Patients With Acute Coronary Syndrome - Chindy, Chindy; Diana, Diana (The International Journal of Medical Science and Health Research, 2024)
Background: The literature surrounding quality improvement initiatives in healthcare, particularly in the context of acute coronary syndrome (ACS), has evolved significantly over the past few decades. Literature Review: The literature review on quality improvement initiatives in acute coronary syndrome (ACS) reveals a complex landscape of interventions and outcomes that are influenced by various factors, including context, implementation fidelity, and the nature of the interventions themselves. The systematic review by (C Conry et al., 2012) highlights the evolution of hospital-based quality improvement efforts over a decade, pointing out the predominance of interpersonal interventions aimed at patient satisfaction, while technical interventions, which are more likely to yield measurable improvements in outcomes, are less common. Conclusion: In conclusion, the literature underscores the multifaceted nature of quality improvement initiatives in ACS, revealing that while significant advancements have been made, challenges remain in terms of implementation, adherence, and contextual adaptation. The effectiveness of these initiatives is contingent upon robust leadership, standardized protocols, and ongoing evaluation of quality indicators. Future research should aim to develop tailored strategies that consider local contexts and address barriers to implementation, ultimately enhancing the quality of care for patients with acute coronary syndrome.